PEMANFAATAN DAUN POHPOHAN (Pilea melastomoides) DAN BUAH KALAMANSI (x Citrofortunella microcarpa) DALAM PEMBUATAN PERMEN JELI [Utilization of Pohpohan Leaves and Calamansi in Jelly Candy Making] - Yuniwaty Halim; Irani Ratnasari; Dela Rosa (FaST : Jurnal Sains dan Teknologi, 2020)
Pohpohan leaves and calamansi are known to contain high calcium and vitamin C, respectively. Their utilization in food products is still limited. Jelly candy is one of the food products that are widely consumed. The aims of this research were to determine the addition of pohpohan leaves flour and calamansi juice in jelly candy making, and to determine the ratio of Îº-carrageenan:konjac to obtain jelly candy with the best characteristics. The jelly candy was made by adding pohpohan leaves flour (2, 4, 6 gram per 100 gram jelly candy formulation) and  calamansi juice with water:calamansi juice ratio of 0:1, 1:1, and 1:2. Afterwards, different ratio of carrageenan:konjac of 1:1, 2:1, and 3:1 was also applied in jelly candy making. Addition of pohpohan leaves flour, calamansi juice and ratio of carrageenan:konjac affect the characteristics of jelly candy obtained. Based on hedonic test, the most preferred jelly candy was jelly candy that was added with 4 gram of pohpohan leaves flour, calamansi juice with ratio 0:1 (water to calamansi juice) and ratio between Îº-carrageenan:konjac of 3:1. The best jelly candy has pH of 3.81 ± 0.04, total titratable acidity of 3.07 ± 0.21% and hardness value of 125.86 ± 2.40 g. The best jelly candy also contains 206.5850 ± 13.42 mg/ 100g calcium content and 0.021 ± 0.001 mg/mL of vitamin C.AbstrakDaun pohpohan dan kalamansi diketahui mengandung kalsium yang tinggi dan vitamin C. Akan tetapi, pemanfaatanya dalam produk pangan masih terbatas. Permen jeli merupakan salah satu produk pangan yang banyak dikonsumsi. Tujuan penelitian ini adalah untuk menentukan penambahan tepung daun pohpohan dan sari buah kalamansi dalam pembuatan permen jeli, serta untuk menentukan rasio karagenan:konjak untuk menghasilkan permen jeli dengan karakteristik terbaik. Permen jeli dibuat dengan menambahkan tepung daun pohpohan (2, 4, 6 gram per 100 gram formulasi permen jeli) dan sari buah kalamansi dengan rasio air:sari buah kalamansi sebesar 0:1, 1:1, dan 1:2. Selanjutnya, berbagai rasio karagenan:konjak sebesar 1:1, 2:1, dan 3:1 juga digunakan dalam pembuatan permen jeli. Berdasarkan uji hedonik, permen jeli terpilih adalah permen jeli yang ditambahkan dengan 4 gram tepung daun pohpohan, rasio air:sari buah kalamansi 0:1, serta rasio karagenan:konjak sebesar 3:1. Permen jeli ini memiliki nilai pH 3,81 ± 0,04, total asam tertitrasi 3,07 ± 0,21%, dan nilai hardness 125,86 ± 2,40 g. Permen jeli ini juga mengandung kalsium sebesar 206,59 ± 13,42 mg/100g dan vitamin C sebesar 0,021 ± 0,001 mg/ml.